Correlation of preprocedural ultrasound estimated epidural depths in transverse median and posterior sagittal oblique view and body mass index with procedural epidural depths in patients scheduled for surgery under lumbar epidural anaesthesia - Harshvardhan Awasthi (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Preprocedural lumbar ultrasound (US) is employed for the estimation of epidural depth (ED). This study observed the correlation of preprocedural ED in transverse median (TM), parasagittal oblique (PSO) view, and body mass index (BMI) with procedural ED. Methods: In a prospective study, 100 female patients, aged 40–65 years, with American Society of Anesthesiologists physical status I/II, BMI 18.5–30 kg m−2 scheduled for surgeries under lumbar epidural blocks were included. In the TM group, preprocedural ultrasonography (USG) was performed in TM view and ED was calculated, whereas in the PSO group, the paramedian sagittal view was used and corresponding markings were done for epidural needle insertion in the midline and paramedian planes, respectively. The primary outcome was the correlation of procedural ED and preprocedural ED in TM and PSO views, respectively. The secondary outcomes included correlation of procedural ED with BMI, comparability of preprocedural, and procedural ED in TM and PSO views. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) v19.0 (International Business Machines, USA). Results: The preprocedural and procedural ED was less in the TM group (4.43 ± 0.75 and 4.44 ± 0.75 cm) in comparison to those in the PSO group (4.86 ± 0.53, 4.90 ± 0.54; P = 0.001). Strong correlation was observed in preprocedural and procedural ED [r2 = 0.996 and 0.995]. The procedural ED had strong correlation with BMI [r2 = 0.600, P = 0.001] in the TM group, and weak correlation [r2 = 0.367] in the PSO group [P = 0.01]. The procedural ED was comparable to preprocedural ED in TM and PSO groups. Conclusion: Preprocedural US scanning provides an accurate estimate of actual EDs in TM and PSO view.